2002
DOI: 10.1001/jama.288.15.1874
|View full text |Cite
|
Sign up to set email alerts
|

Six-Year Follow-up of Preventive Interventions for Children of Divorce

Abstract: In adolescents of divorced parents, the mother program and the mother plus child program reduced symptoms of mental disorder; rates of diagnoses of mental disorder; levels of externalizing problems; marijuana, alcohol, and other drug use; and number of sexual partners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
247
1
11

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(281 citation statements)
references
References 40 publications
17
247
1
11
Order By: Relevance
“…Overall, findings of long-term group differences on obesity, health behaviors and blood pressure reinforce earlier demonstrations of the broad range of benefits from behavioral family intervention for children with or at risk for behavior problems [30][31][32][33][34][35][56][57][58][59][60] and are consistent with theoretical models that implicate parenting in the promotion of healthy physical development. Reductions in BMI among overweight Australian children whose parents participated in a treatment program to improve parenting (eg, responsiveness) also provide support for this approach.…”
Section: Discussionsupporting
confidence: 80%
“…Overall, findings of long-term group differences on obesity, health behaviors and blood pressure reinforce earlier demonstrations of the broad range of benefits from behavioral family intervention for children with or at risk for behavior problems [30][31][32][33][34][35][56][57][58][59][60] and are consistent with theoretical models that implicate parenting in the promotion of healthy physical development. Reductions in BMI among overweight Australian children whose parents participated in a treatment program to improve parenting (eg, responsiveness) also provide support for this approach.…”
Section: Discussionsupporting
confidence: 80%
“…It showed that the divorce had an effect of on adolescents' alcoholism mainly in the last month, and that positive involvement of the father after divorce -was a protective factor relating to alcoholism in families who have experienced divorce. Wolchik et al [29] claim that compared to teens of un-divorced parents, teenagers of divorced parents-have a higher risk of developing mental disorders, to drop out of school or get pregnant.…”
Section: Behavioral Problems and Depressionmentioning
confidence: 99%
“…Given that many effects of terrorism on children can be indirect, interventions that improve parental functioning may reduce the transmission of effects to children (eg, Dybdahl, 2001;Forgatch and DeGarmo, 1999;Wolchik et al, 2002). It is widely assumed that similar effects can be achieved through interventions with teachers.…”
Section: Terrorism Risk and Interventions: A Developmental Resiliencementioning
confidence: 99%